ANALISIS SIFAT FISIK DAN KIMIA TANAH TERHADAP INTENSITAS PENYAKIT BUSUK BUAH KAKAO (Phytophthora Palmivora) - Arifudin Bakrie (Media Agribisnis, 2017)
The aim of this research is to know the intensity of black pod in the field and to analyze the physical and chemical properties of the soil affecting the intensity of late of black pod caused by Phytophthora palmivora. This research was conducted from January to February 2017, which was conducted in cocoa plantation in South Lasalimu sub-district and Siotapina sub-district and laboratory of Agriculture Faculty of Halu Oleo University. This research was conducted by conducting a survey on cocoa farming for observation of disease intensity and soil sampling. The observed variables were disease intensity in the field, physical and chemical properties of the soil, and the relationship of disease intensity with soil physical and chemical properties. The results showed that the intensity of black pod flies in the field ranged from 56.44 to 66.79%. Physical properties and soil chemistry that have a direct influence increase the intensity of black pod is the fraction of sand, moisture content, pH, K content, and saturation basa while the direct effect decrease is C-organic, N total, Salinity, P available, CEC, clay, and porosity of the soil. Keywords: P. palmivora, black pod, soil physical properties, soil chemical properties